The side effect registry immuno-oncology (SERIO) - a tool for systematic analysis of immunotherapy-induced side effects - Ertl, Carolin; Ruf, Theresa; Mentzer, Dirk; Kong, Mingzi; Kramer, Rafaela; Bergwelt-Baildon, Michael von; Subklewe, Marion; Tomsitz, Dirk; Ascierto, Paolo A.; Dummer, Reinhard; Gogas, Helen; Lebbé, Celeste; et al. (European journal of cancer, 2024)
Background - Immunotherapies such as immune checkpoint inhibitors (ICI) are effective in multiple tumor entities but induce a plethora of side effects. Comprehensive real-world analyses are essential to identify new signals, characterize diagnostic features, enable risk assessment, determine pathomechanisms, assess effectiveness of side effect management and compare tumor outcomes. - Methods - The international online `Side-Effect Registry Immuno-Oncology´ (SERIO; www.serio-registry.org) collects rare, complex, and severe immunotherapy-induced side effects across all tumor entities with a strong focus on ICI-induced immune-related adverse events (irAE). The relational database management system (RDMS) contains structured data on patient and tumor characteristics, type of immunotherapy, treatment of side effects, and outcome of tumor and irAE. Data are captured within 25 organ modules including new modules for immune effector cell-associated neurotoxicity syndrome (ICANS) for CAR-T-cell therapies and cytokine release syndrome (CRS) for bispecific antibodies. Information on biological samples is gathered. - Results - A total of 1398 irAE cases have been documented by 58 centers from 13 countries in patients with 17 tumor types. IrAEs were induced by nine different immunotherapies including tebentafusp and CAR-T cell therapies, and resulted, among others, in neurological (7.6%), pulmonary (4.0%), and cardiac toxicities (2.9%). 50.0% of all irAEs were graded severe or life-threatening and 23.0% of patients received second-line therapy for steroid-refractory or steroid-dependent irAE. SERIO has contributed to 44 original publications on topics ranging from irMyocarditis to irEncephalitis to long-term persistent sequelae of immunotherapy. - Conclusions - A reliable evidence base is crucial for decision-making in rare, complex or therapy-refractory irAE. SERIO can help optimize side effect management and thereby reduce morbidity and mortality induced by immunotherapy.
Online verfügbar: 23. Dezember 2023, Artikelversion: 22. Januar 2024
Gesehen am 07.08.2024